A remark on the slice map problem - Muneo Chō; Tadasi Huruya (International Journal of Mathematics and Mathematical Sciences)
It is shown that there exist a σ-weakly closed operator algebra A˜, generated by finite rank operators and a σ-weakly closed operator algebra B˜ generated by compact operators such that the Fubini product A˜⊗¯FB˜ contains properly A˜⊗¯B˜.